2020
DOI: 10.1021/acsami.0c05664
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Cation-Exchange Membranes with Polyelectrolyte Multilayers to Tune Ion Selectivity in Capacitive Deionization

Abstract: Capacitive deionization (CDI) is a desalination technique that can be applied for the separation of target ions from water streams. For instance, mono- and divalent cation selectivities were studied by other research groups in the context of water softening. Another focus is on removing Na + from recirculated irrigation water (IW) in greenhouses, aiming to maintain nutrients. This is important as an excess of Na + has toxic effects on plant growth by decreasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 78 publications
0
33
0
Order By: Relevance
“…The first is that the selectivity changes strongly during a CDI cycle, i.e., it depends on the moment within a cycle, and likely also on the durations of the charge and discharge steps in a full cycle. 123 The second conclusion is that the actual realized selectivity can be much lower than the maximum calculated selectivity, which in this case is a value significantly above 100. This is in line with the conclusion presented by Porada et al 78 Careful design of the electrodes and the cell will be essential in obtaining selectivity values that in practice come closer to the ideal value.…”
Section: View Article Onlinementioning
confidence: 80%
See 2 more Smart Citations
“…The first is that the selectivity changes strongly during a CDI cycle, i.e., it depends on the moment within a cycle, and likely also on the durations of the charge and discharge steps in a full cycle. 123 The second conclusion is that the actual realized selectivity can be much lower than the maximum calculated selectivity, which in this case is a value significantly above 100. This is in line with the conclusion presented by Porada et al 78 Careful design of the electrodes and the cell will be essential in obtaining selectivity values that in practice come closer to the ideal value.…”
Section: View Article Onlinementioning
confidence: 80%
“…8B). 123 While the bare CMX membrane had a r of E0.5 for Na + over Mg 2+ , the selectivity of the PEM-coated membrane was found to be E3. This switch in selectivity was attributed to the charge rejection experienced by ions with higher valence (Fig.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…MCDI water softening performance is determined by feed water chemistry, hydrated ion radius, ion valence, electrode and IEM construction and materials, operating modes and operating conditions [ 15 , 16 , 23 , 24 ]. Hou and Huang [ 15 ] observed preferential adsorption of ions with smaller hydrated ion radius, larger charge valence and higher initial concentration in a batch mode CDI.…”
Section: Introductionmentioning
confidence: 99%
“…IEM selective permeation toward specific ions is governed by the affinity of IEM toward the ions, ion concentration outside the IEM and ion mobility inside the IEM and can be enhanced by membrane surface modification [ 25 ]. Specific IEM modifications such as replacing CEM with Ca-alginate [ 16 ] and coating polyelectrolyte multilayers onto the CEM [ 24 ] have been employed to tune ion selectivity in MCDI. He et al [ 23 ] observed that selectivity of calcium ions was enhanced under lower applied current and shorter hydraulic retention time in a flow-electrode CDI.…”
Section: Introductionmentioning
confidence: 99%